2022
DOI: 10.3390/diagnostics12123047
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Machine Learning Models to Classify Artery Stenosis for Automated Generating Ultrasound Report

Abstract: Duplex ultrasonography (DUS) is a safe, non-invasive, and affordable primary screening tool to identify the vascular risk factors of stroke. The overall process of DUS examination involves a series of complex processes, such as identifying blood vessels, capturing the images of blood vessels, measuring the velocity of blood flow, and then physicians, according to the above information, determining the severity of artery stenosis for generating final ultrasound reports. Generation of transcranial doppler (TCD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For Transcranial Doppler (TCD), the accuracy of random forest models to predict stenosis ranged from 0.67 to 0.86. The study thus indicated that machine learning-based models accurately classify artery stenosis [57].…”
Section: Artery Stenosismentioning
confidence: 78%
See 1 more Smart Citation
“…For Transcranial Doppler (TCD), the accuracy of random forest models to predict stenosis ranged from 0.67 to 0.86. The study thus indicated that machine learning-based models accurately classify artery stenosis [57].…”
Section: Artery Stenosismentioning
confidence: 78%
“…The high accuracy metrics support AI as an adjunct tool in stroke diagnostics [16], [24]. Machine learning models have been developed and shown promising outcomes in classifying stenosis, diagnosing moyamoya disease, brain arteriovenous malformations, cerebrovascular thrombosis [53], [55], [57], [58]. Various neural networks can aid in accurate and quick diagnosis & segmentation of cerebral aneurysms, a task which can be labour intensive if done manually [21], [31].…”
Section: Detection and Diagnosis: Stroke -Swift And Precisementioning
confidence: 99%